Trends in fall‐related mortality and fall risk increasing drugs among older individuals in the United States, 1999–2017. Issue 8 (16th February 2021) - Shaver, Amy L.; Clark, Collin M.; Hejna, Mary; Feuerstein, Steven; Wahler, Robert G.; Jacobs, David M.
Abstract: Background: Previous studies have demonstrated increasing mortality due to falls among older adults. The objective of this study was to determine whether there was an increase in fall risk increasing drug prescribing and if this is concurrent with an increase in fall‐related mortality in persons 65 years and older in the United States. Methods: The study is a serial cross‐sectional analysis utilizing data from both the National Vital Statistics System (NVSS) and the medical expenditure panel survey (MEPS) for years 1999–2017. Adults aged 65 years and older were evaluated for death due to falls from the NVSS and for prescription fills of fall risk increasing drugs per the Stopping Elderly Accidents, Deaths, and Injuries‐Rx (STEADI‐Rx) fall checklist from the MEPS. Results: The analysis included 374 972 fall‐related mortalities and 7 858 177 122 fills of fall risk increasing drugs. 563 037 964 persons age 65 and older received at least one fall risk increasing drug. Age‐adjusted mortality due to falls increased from 29.40 per 100 000 in 1999 to 63.27 per 100 000 in 2017. The percent of persons who received at least one prescription for a fall risk increasing drug increased from 57% in 1999 to 94% in 2017 ( p for trend <.0001). Conclusions and relevance: Both use of fall risk increasing drugs and mortality due to falls are on the rise. Fall risk increasing drugs may partially explain the increase in mortality due to falls; this cannot be firmly concluded from the current study. Future research examining the potential relationship between fall risk increasing drugs and fall‐related mortality utilizing nationally representative person‐level data are needed.